PENGARUH UPAH, MODAL, BAHAN BAKU DAN TENAGA KERJA TERHADAP PRODUKSI INDUSTRI KERIPIK DI DESA SAREE LEMBAH SEULAWAH ACEH BESAR - Afriansyah Afriansyah; Suriani Suriani (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract This study aims to determine the effect of wages, capital, raw materials and labor on the production of chips in Saree Village, Lembah Seulawah District, Aceh Besar Regency. In this study, the independent variables used are variable of wages, capital, raw materials and labor. While the dependent variable is the production variable. The data used in this study are primary data directly from the first source, namely the owner of the chips business in Saree Village. The analytical model used is a multiple linear regression model and classic assumption test. The results of the analysis show that individually the variables of capital and raw materials have a positive and significant influence on the production of chips, while the variable wage and labor have a negative influence on the production of chips. While simultanly, all the independent variables namely wages, capital, raw materials and labor have a positive and significant effect on the production of chips. The role of government is needed for the development and improvement of small industrial production.Keywords: Wage, Capital, Raw Materials, Labor, Production of Chips